Photodeposition of Au and Pt on ZnO and TiO(2) - S. A.C. Carabineiro (2010)
Au and Pt were loaded (1 wt.%) on ZnO and TiO(2) supports from different sources using a photodeposition method. The catalytic activity of the prepared materials was tested in CO oxidation. It is shown that Pt gives better results for ZnO supported catalysts, while Au is pronouncedly more active in the case of TiO(2). This might be related to the smaller particle size of Au when supported on TiO(2) and the stronger metal-support interaction effect, which are important factors in catalysis by Au. In the case of Pt catalysts, the dependence on the support is not so marked, which may be attributed to the reaction taking place predominantly on the bare metal surface.